The kinematic analysis of the grab and the track start in swimming - Jorgic, B.; Puletic, M.; Stankovic, R.; Okicic, T.; Bubanj, S.; Bubanj, R. (Facta Universitatis: Series Physical Education and Sport, 2010)
The winner in swimming is often decided by hundredths of a second, and therefore, all the elements of the race must be practiced. The start in swimming, together with the other elements of the race, is very important for achieving better results in competitions. Nowadays, swimmers use two start techniques: the grab and track start. The aim of this study is to determine the statistically significant differences in certain kinematic parameters between the grab and track start among competitive swimmers, cadet selection. The sample consisted of 6 competitive swimmers, 15 years of age ± SD, who belong to the cadet selection of the swimming club "Argiroupoli Nautical Club"from Athens (Greece). Three swimmers performed the grab start, while the other three performed the track start. This study involved 8 kinematic parameters: flight length (FL), flight time (FT), ascending angle (AA), angle of entry (AE), velocity of the centre of mass at take-off (VCMT), velocity of head movement at takeoff (VHMT), velocity of hand movement at takeoff (VHdMT) and velocity of hip movement at takeoff (VHpMT). In order to determine the statistically significant difference between the grab and track start, we used the t-test for each kinematic parameter. According to the results obtained in this research, we can conclude that there is no statistically significant difference between the grab and track start, except in the parameter AA (p=0.04). That is why an advantage cannot be given to one of these start techniques. Instead of that, the regular and intensive drill of a chosen start technique should be applied. While doing that, the choice of a start technique must be adapted to the swimmer's abilities and it must increase his competitive efficiency..